#TITLE_ALTERNATIVE# - RIZKY FAUZIANDINI (NIM: 18213028), AIREN
The aspired ideal city is a city that can give a sense of security, safety, relieve from problems, and providing a means for sufficient city services. The concept of ideal city seems closer in definition with the referred concept of smart city. A quality of service as in the depiction of an ideal city is a hard thing to achieve by a city as a big system which consists of multiple dimensions and service domains. Nonetheless, no matter how big the problems are, it is the duty of city government to serve at its best for solving the problems. To achieve that goal, city gradually needs a set of indicators used to guide the city development and to measure how improved the city has been. The city indicators used can be the characteristics of the depicted ideal city so that the city development can be directed towards a better and ideal city. The ideal city indicators will be referred from ISO 37120, Garuda Smart City Model, India Smart City, European Union Smart City, and Standar Pelayanan Minimal. The means to provide a quality of service as in the depicted ideal city is by enabling initiatives. Initiative is a mean or action to improve a city indicator(s). Initiative can be delivered with or without information technology, formulated through a long iterative process of design thinking which is started from understanding the indicator(s), to ideas brainstorming, and determine initiative(s) that can fulfil the indicator(s). However, sometimes initiative(s) cannot fulfil the indicator(s) successfully. For city initiatives to fulfil the indicator(s) successfully, it is necessary to identify and analyse a set of components from an initiative to break down the steps needed to be done in an initiative and map the initiative(s) to their respective fulfilled indicator(s). Thus, there is a need for a framework that can break down initiative(s) to their components thoroughly and in a structured manner. These components come from the result of study on the initial purpose of the framework and on some basic components of a framework which is referred from COBIT, TOGAF 9.1, and Zachman Framework. Eventually, a framework, which will be called Kerangka Kerja Inisiatif Teknologi Informasi (KKITI), with a breakdown of a total of 11 indicators and 15 initiatives on natural environment domain and 5 indicators and 6 initiatives on energy domain is successfully produced. Based on the evaluation result, KKITI for development towards a better city is successful in fulfilling the needs of its components and can be applied by city government in a structured manner on a case study of a city development.